Efficiency of using a physiological portrait of a university student in physical education / Valentina Talantseva, Nadezhda Altynova and Nadezhda Pianzina - Talantseva, Valentina; Altynova, Nadezhda; Pianzina, Nadezhda (Universiti Teknologi MARA Cawangan Sarawak, 2019)
The modern higher school has increased requirements not only for the training of highly qualified specialists with a certain amount of personal and professional qualities, good health and a sufficient level of physical fitness. However, the present students need the indicators of physical development, functional resources and right level of physical fitness. The purpose of the study was to justify the efficiency of using the "Physiological portrait of a university student" in physical education. To assess the basic indicators of health and fitness of students, a specially developed "Physiological portrait of a university student" (PhPUS) was used. It included indicators of physical development, functional capabilities of basic physiological systems and physical abilities of students. The practical significance of the study included comparing the parameters of PhPUS in the beginning and the end of the academic year. Another study on PhPUS blocks indicated improvement in the students' indices of physical development, functional indices of the main physiological systems and physical fitness. PhPUS for monitoring the physical health of students could help identifying the necessary measures to improve the process of physical education.